PENGEMBANGAN MEDIA ULTA (ULAR TANGGA) PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Anggraini, Suci; Dewi, Galuh Kartika; Rahmawati, Ery (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of students and their lack of active involvement during lessons. The aim of the study is to determine the feasibility of the ULTA (Snakes and Ladders) media and to describe students’ learning outcomes after using the media in the IPAS subject for fifth-grade students in elementary school. The method used is Research and Development (R&D), referring to the Borg & Gall model, which has been simplified into seven main stages. Expert validation shows that the ULTA media received very high feasibility scores, namely 92.5% from media experts and 93.3% from subject matter experts. The media takes the form of a jumbo-sized board game equipped with smart cards, question cards, command cards, educational images, and a large dice. The feasibility of the media was tested through a comparison of students' pretest and posttest scores, which showed a significant increase, with the average score rising from 40 to 80. The N-Gain score obtained was 2, categorized as “High,” indicating a substantial improvement in students' understanding. Based on this research, it can be concluded that the ULTA learning media is effective for use in IPAS instruction and can enhance students’ academic achievement. Additionally, the media provides a fun and interactive learning experience, thereby encouraging students’ active engagement during the learning process.